Wave scattering by many small bodies and applications. - Ramm, Alexander G.; Rona, A. (My University, 2011)
Wave scattering problem by many bodies is studied in the case when the bodies are small, ka 1, where a is the characteristic size of a body. The limiting case when a → 0 and the total number of the small bodies is M = O(a−(2−κ)), where κ ∈ (0, 1) is a number, are studied.